1994
DOI: 10.1007/bf00418373
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human GLUT4 in mice results in increased insulin action

Abstract: Summary Glucose metabolism was evaluated in transgenic mice expressing the human GLUT 4 glucose transporter. Fed GLUT 4 transgenic mice exhibited a 32 % and 56 % reduction in serum glucose and insulin and a 69 % and 33 % increase in non-esterified fatty acid and lactate levels, respectively. Transgenic mice exhibited a significant increase in whole-body glucose disposal during a euglycaemic-hyperinsulinaemic clamp. Insulin-stin'mlated glucose uptake in isolated soleus muscles and adipocytes was greater in tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 57 publications
4
26
0
Order By: Relevance
“…The data presented here in regard to the basal (i.e., sedentary) state are in agreement with previously published reports using GLUT4 (7,15,38) and HK II (6,12,16,27) transgenic mice. That is, GLUT4 but not HK II overexpression increases basal MGU.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The data presented here in regard to the basal (i.e., sedentary) state are in agreement with previously published reports using GLUT4 (7,15,38) and HK II (6,12,16,27) transgenic mice. That is, GLUT4 but not HK II overexpression increases basal MGU.…”
Section: Discussionsupporting
confidence: 82%
“…That is, GLUT4 but not HK II overexpression increases basal MGU. During insulin stimulation, it has been reported that GLUT4 overexpression increases whole body glucose disposal in vivo (7,39) and MGU in vitro (7,15). Hansen et al (15) go on to demonstrate that GLUT4 overexpression augments postexercise MGU.…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that results that differ do so due to technical differences which generally make the preparations less physiological. These include the use of anaesthesia Lombardi et al 1997;Marshall et al 1999), in vitro preparations (Deems et al 1994;Hansen et al 1995;Tsao et al 1996;Lombardi et al 1997;Marshall et al 1999), suprapharmacological insulin doses Ren et al 1995;Marshall et al 1999) and prolonged fasting (Ren et al 1995). With regard to the latter two, it is noteworthy that, when Ren et al (1995) in marked reduction in glycogen content and weight, or suprapharmacological insulin, GLUT4 overexpression increased glucose utilization during an insulin clamp.…”
Section: Discussionmentioning
confidence: 99%
“…In a related study a high 100 μM dose of BPA stimulated an increase in the glucose transporter GLUT4 and glucose uptake into 3T3-F442A adipocytes in cell culture [112]. In a separate study of transgenic mice over expressing the GLUT4 gene, increased basal and insulin-induced glucose uptake was observed in whole body and in isolated adipocytes [113]. Whether the mouse 3T3 cell lines, which are relatively insensitive to estrogen, are an appropriate model to study the effects of BPA in vitro remains to be determined.…”
Section: Developmental Effects On Metabolismmentioning
confidence: 97%